MODEL KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEMBANGUN EKOSISTEM RELIGIUS MELALUI PROGRAM TAHFIDZ UNTUK MENINGKATKAN PRESTASI NON-AKADEMIK SISWA DI SD M PUCANG GADING - Mukhammad Sobirin; Sutama Sutama; Achmad Fathoni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the transformational leadership model of the principal in developing a religious ecosystem through the Tahfidz Al-Qur’an program and its contribution to improving students’ non-academic achievements at SD Muhammadiyah Pucang Gading. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observations, and documentation involving the principal, Tahfidz teachers, classroom teachers, students, and parents. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the principal implemented transformational leadership through four dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These dimensions were reflected in the integration of the Tahfidz program into the school curriculum, the establishment of religious habits, teacher professional development, and strong collaboration with parents. The implementation of these strategies successfully created a religious ecosystem characterized by Qur’anic memorization culture, worship habituation, exemplary behavior, and a supportive learning environment. As a result, students demonstrated improvements in non-academic achievements, including success in religious competitions, enhanced discipline, self-confidence, responsibility, and leadership skills.